2019
DOI: 10.1002/ajpa.23846
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic equifinality and rethinking the diet of Australopithecus anamensis

Abstract: Objectives: Australopithecus anamensis has comparable δ 13 C enamel values to Ardipithecus ramidus, and both have been characterized as C 3 feeders in open woodland habitats similar to "savanna" chimps. Unlike Ar. ramidus and "savanna" chimps, A. anamensis shows a derived dentognathic morphology for tough foods and a dental microwear pattern similar to the C 3 -C 4 -mixed-feeding A. afarensis. Here I test the hypothesis that changing the variables (ε * enamel-diet , δ 13 C C3, δ 13 C C4 values) used to calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 159 publications
(342 reference statements)
0
11
0
Order By: Relevance
“…Although microwear data contrast those of dentognathic morphology and imply soft foods were regularly consumed (Grine et al, 2012), A. anamensis' dental microwear patterns are similar to those of the C3-C4 mixed feeding A. afarensis (Grine et al, 2006;Ungar et al, 2010). Quinn (2019) In a common thread, we suggest a gradual and stepwise but not necessarily abrupt behavioral shift underpins the earliest known stone tool making behaviors as represented by LOM3. Tools are used by extant chimpanzees to forage (Boesch and Boesch, 1990;Haslam, 2014;Haslam et al, 2009;Marchant and McGrew, 2005); thus tool-assisted foraging may be a shared ape-human behavioral trait also present in the earliest hominins (Toth and Schick, 2009).…”
Section: Pliocene Hominin Dietary Niche Expansion and Stone Tool Originsmentioning
confidence: 70%
See 1 more Smart Citation
“…Although microwear data contrast those of dentognathic morphology and imply soft foods were regularly consumed (Grine et al, 2012), A. anamensis' dental microwear patterns are similar to those of the C3-C4 mixed feeding A. afarensis (Grine et al, 2006;Ungar et al, 2010). Quinn (2019) In a common thread, we suggest a gradual and stepwise but not necessarily abrupt behavioral shift underpins the earliest known stone tool making behaviors as represented by LOM3. Tools are used by extant chimpanzees to forage (Boesch and Boesch, 1990;Haslam, 2014;Haslam et al, 2009;Marchant and McGrew, 2005); thus tool-assisted foraging may be a shared ape-human behavioral trait also present in the earliest hominins (Toth and Schick, 2009).…”
Section: Pliocene Hominin Dietary Niche Expansion and Stone Tool Originsmentioning
confidence: 70%
“…Tejada-Lara et al (2018) suggested the ε*enamel-diet value of mammalian herbivores is predicted by body mass and gut physiology, producing ε*enamel-diet values ranges between +9 and +16‰. The use of specific ε*enamel-diet values can impact dietary reconstructions (Quinn, 2019).…”
Section: Faunal  13 Cec and  18 Oec Analysesmentioning
confidence: 99%
“…We caution the use of a linear mixing model in a geographic and temporal setting offering numerous food items and a large range in C 3 plant δ 13 C values (e.g., Kohn, ), which commonly results in isotopic equifinality (e.g., Quinn, ). Moreover, the two tissue types (i.e., enamel and hair) record different aspects of diet (Ambrose & Norr, ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on previously analysed bulk enamel δ 13 C values, we calculated the percentage of marine/estuarine dietary resources ('%Marine') to further differentiate dietary practices amongst the 11 Harris Creek burials. We assumed pre-industrial atmospheric CO 2 δ 13 C values and used a combination of methods of Schwarcz et al (1985) and Cerling and Harris (1999) as summarized by Quinn (2019). Diet-enamel δ 13 C spacing (ε*)=12‰ after Lee-Thorp et al (1989); C 4 range (marine/estuarine) and C 3 (terrestrial/freshwater) δ 13 C endmembers are À12‰ and À28‰, respectively (Schoeninger and DeNiro 1984;Kohn 2010).…”
Section: Methodsmentioning
confidence: 99%